2012
DOI: 10.3174/ajnr.a3198
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Diffusion in Neurocysticercosis: Circumstances of Appearance and Possible Natural History Implications

Abstract: BACKGROUND AND PURPOSE:Few studies discuss DWI findings in patients with NCC, and their conclusions are variable and contradictory. The aim of our study was to describe DWI findings of a cohort of patients with NCC, emphasizing the frequency of reduced diffusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…Once the oncosphere has passed into the parenchyma, it grows and evolves through vesicular, colloidal, granular-nodular, and calcified phases. In the vesicular phase, the host tends to show immune tolerance and in most cases there is no surrounding parenchymal reaction; the larva lives inside a translucent liquid-filled cystic structure surrounded by a thin membrane, where it can remain viable from a few months to several years 10 . Figure depicts circumscribed, rounded, hypodense areas, varying in size and number, without enhancement by contrast media.…”
Section: Distinguishing Between Seizures and Epilepsy As They Relate mentioning
confidence: 99%
See 1 more Smart Citation
“…Once the oncosphere has passed into the parenchyma, it grows and evolves through vesicular, colloidal, granular-nodular, and calcified phases. In the vesicular phase, the host tends to show immune tolerance and in most cases there is no surrounding parenchymal reaction; the larva lives inside a translucent liquid-filled cystic structure surrounded by a thin membrane, where it can remain viable from a few months to several years 10 . Figure depicts circumscribed, rounded, hypodense areas, varying in size and number, without enhancement by contrast media.…”
Section: Distinguishing Between Seizures and Epilepsy As They Relate mentioning
confidence: 99%
“…Although these pathological changes are responsible for clinical manifestations, such as seizure and headache, they may also be completely asymptomatic. Finally, when the cyst dies, it may disappear or become an inactive calcified nodule of homogenous high density on CT, or low intensity on proton-weighted MRI 9,10 . A classification based on the viability and location of the parasite in the CNS has been proposed: active, when the parasite is alive; transitional or degenerative, if it is in the colloidal and granular-nodular phase; or inactive, if there is evidence of its death 11 .…”
Section: Distinguishing Between Seizures and Epilepsy As They Relate mentioning
confidence: 99%
“…And it disappears in the 'early' granular nodular stage when the contents changes from viscous fluid to solid material. The overall role of DWI comes in these stages by helping in the identification of the scolex [35]. Diffusion tensor imaging (DTI) is not used routinely in the diagnosis of NCC.…”
Section: Role Of Advanced Mri Sequences Dwi/dtimentioning
confidence: 99%
“…MRI is the best test for definition of the cyst stage in their evolution in the brain on T1, T2, FLAIR sequences, including the inflammatory aspects when using enhanced images with gadolinium infusion ( Figures 3A, B and C) 29 although not as accurate in detection of calcifications. Diffusion weighted images were demonstrated as better defining the scolex and increasing the confidence for the NCC diagnosis by MRI 30 . A recent review on NCC showed that MRI findings are better predictive for the stage of the cysts and diffusion-weighted images and apparent diffusion coefficient maps allowing better demonstration of the cysticerci in their colloidal phase.…”
Section: The Quest For the Neuroimagingmentioning
confidence: 99%
“…With cerebral cyst degeneration there is a contrast enhancement of the lesion surrounded by edema on CT as well as high signal images on MRI T2 sequences and gadolinium enhancement on T1 images supposedly due to inflammatory reactions 4,5 . Epilepsy, in general grounds, is defined by unprovoked seizures in more than one occasion 6 and usually correlates with the most probable condition directly involved on its development.…”
mentioning
confidence: 99%